Ubiquinol supplementation modulates energy metabolism and bone turnover during high intensity exercise. Issue 9 (14th August 2020) - Diaz-Castro, Javier; Mira-Rufino, Pablo Javier; Moreno-Fernandez, Jorge; Chirosa, Ignacio; Chirosa, Javier Luis; Guisado, Rafael; Ochoa, Julio J.
Abstract : Bone and energy metabolism are profoundly influenced by exercise. Abstract : Bone and energy metabolism are profoundly influenced by exercise. The objective of this study was to determine for the first time whether a short-term supplementation with ubiquinol could have a modulating effect on bone turnover and energy metabolism associated with strenuous exercise. The participants ( n = 100 healthy and well-trained firemen) were randomly divided into two groups: ubiquinol group (ubiquinol (200 mg day −1 )) and control group (placebo) for two weeks. The protocol consisted of conducting two identical strenuous exercise tests with a rest period between tests of 24 h. Blood samples were collected before supplementation (basal value) (T1), after supplementation (T2), after the first physical exercise test (T3), after 24 h of rest (T4), and after the second physical exercise test (T5). Parathyroid hormone (PTH), osteocalcin (OC), osteoprotegerin (OPG), osteopontin (OPN), sclerotin (SOST), alkaline phosphatase (AP), adrenocorticotropin (ACTH), insulin, leptin, adrenaline, noradrenaline and peroxisome proliferator activated receptor-γ coactivator-1α (PGC-1α) were determined. Our protocol increased ACTH, SOST, PTH and OC levels, while it decreased OPN. This protocol also increased adrenaline, noradrenaline and PCG-1α, and decreased insulin. After ubiquinol supplementation, PTH, OC, OPG, alkaline phosphatase, leptin, insulin, noradrenaline and PGC-1α levels increased in the supplemented group compared to the control group after the exercise protocol. Strenuous exercise has a clear effect on energy metabolism and bone turnover. These effects are modulated by ubiquinol supplementation, which especially increases the biomarkers of bone formation during strenuous exercise. In addition, ubiquinol has a beneficial effect on the mobilization of energy sources, fact that it could represent an ergogenic and physiological advantage for skeletal muscles.